Ethnobotanical approach in the treatment of kidney diseases: A comparative study in Peruvian indigenous communities - Quispe Silva, Thalia Yohana; Epiquién Chancahuana , Migdonio; Sepúlveda-Loyola, Walter (Ethnobotany Research and Applications, 2025)
Background: Kidney problems are common and often neglected due to limited access to medical care in indigenous communities. As a result, the use of medicinal plants has become a practice deeply rooted in traditional medicine. Identifying the main plants used for this purpose, along with their routes of administration and dosage, provides valuable insight into indigenous therapeutic practices for kidney-related ailments. Methods: A cross-sectional study was conducted between 2024 and 2025 in the indigenous communities of Supayaku and Yamakey in Peru. Sociodemographic data and information on the use of medicinal plants were collected through surveys of indigenous individuals over 18 years of age who had knowledge of plant use for treating kidney problems. Descriptive statistics and logistic regression models were used to analyze the data. Results: The use of medicinal plants differed significantly in Supayaku and Yamakey. Bixa orellana L. was more abundant in Supayaku than in Yamakey, and Equisetum arvense L. was more prominent in Yamakey than in Supayaku (p = 0.02). Administration duration also differed significantly being longer in Yamakey (23.61 days) than in Supayaku (20.46 days) (p = 0.04). In both communities, plants were mainly field collected (78.57% in Supayaku; 98.21% in Yamakey) and mostly used in infusions (98% in Yamakey and 86% in Supayaku). Conclusions: The study documents the diversity of traditional indigenous medicinal practices for treating kidney problems, highlighting significant differences in species, preparation, and administration of medicinal plants. Keywords: Medicinal Plants; Kidney Diseases; Indigenous Peoples; Latin America